EFFECT OF MELATONIN ON NUCLEAR MATURATION OF CAPRINE OOCYTES - KUSHWAH, B S; KHARCHE, S D; AGARWAL, J; SIKARWAR, A K S; PATHAK, J; AGARWAL, S (The Indian Journal of Animal Reproduction, 2022)
Melatonin at the concentrations of 0, 5, 10, 20, 30, 40, and 50 ng/ml was used in maturation medium toassess the impact on in vitro maturation of caprine oocytes. The oocytes from slaughter house derived ovarieswere subjected to in vitro maturation at 38.5°C with 5%CO2. After culture for 27h, over 90% COCs had fullcumulus cell expansion. The degree of cumulus cell expansion remained similar (p>0.05) on increasing melatoninconcentration, however, oocytes incubated in 30 and 50 ng/ml melatonin containing maturation media for 27 h,result in 80% and 18.9% nuclear maturation rate, respectively, which were different (p
Keywords: Caprine; in-vitro maturation; Melatonin; Metaphase II; Oocytes